Chas. Ben. Darwin, Ordinances of the City of Burlington 159 (1856) - (:unkn) unknown (My University, 1856)
§ 9: Empowered the mayor, wharf master, and the fire wardens to give direction to boats containing gun powder, gun cotton, hay, or other combustible materials.
Keywords: GUNPOWDER - TRANSPORTATION